Transient Expression of gusA and gfp Gene in Agrobacterium-mediated Banana Transformation Using Single Tiny Meristematic Bud - Sreeramanan, Subramaniam; Mahmood, Maziah; Abdullah, Mohd Puad; Meon, Sariah; Xavier, Rathinam (Asian Network for Scientific Information, 2006)
Several factors were investigated for the transfer of an intron-containing β-glucuronidase (gusA) and green fluorescent protein (gfp) gene into banana cultivar, Pisang Rastali (AAB) single bud using the Agrobacterium-mediated transformation system. Two disarmed Agrobacterium tumefaciens strains, EHA 101 (pIG121-Hm) and LBA 4404 (pCambia 1304) were evaluated as vector systems. A number of parameters such as pre-culture period of buds prior to inoculation, co-cultivation period, acetosyringone concentration used during co-cultivation in MS medium, methods of wounding, Agrobacterium strains, influence of different bud sizes and post cultivation period were evaluated to maximise transformation efficiency. Agrobacterium tumefacien, EHA101 (pIG121-Hm), a supervirulent strain proved to be significantly better than LBA 4404 (pCambia 1304) based on higher expression intensity and even spread of GUS staining (pIG121-Hm harbours gusA gene only and pCambia 1301 harbour both gusA and gfp gene). The GFP expression was higher than the GUS using Agrobacterium tumefacien, LBA 4404 (pCambia 1304). The results from transient transformation of single tiny meristematic bud suggested that Agrobacterium-mediated transfer of T-DNA to banana cells is highly efficient. By combining the best treatments, an efficient and reproducible transformation procedure has been established for the production of transgenic banana using this system. © 2006 Asian Network for Scientific Information.